The determinant of commertial banks financial performance in Ethiopia - Ketema Sime; Kenenisa Lemmie; Endalew Gutu (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
The study was attempted to investigate determinants of financial performance of commercial banks in Ethiopian by using secondary data. The data were obtained from audited financial statements of five sampled commercial banks for the period of 1997 to 2017 and National Bank of Ethiopia. The study used return on assets (ROA) and return on equity (ROE) as dependent financial performance variable. Moreover, the study used bank specific variables as explanatory variables. Both descriptive statistics and econometrics model specifically fixed effects estimation were used to analyze the relationships of dependent variable with explanatory variables. The major findings of the study shows that bank specific determinants were very important in explaining financial performance of commercial banks. The management efficiency, customer deposit to total asset ratio, capital adequacy ratio, loan to deposit ratio were positively and significantly related to bank’s financial performance. The study recommends that banks put a lot of focus on their own internal processes since bank specific factors have the biggest impact on their profitability. Most importantly, Ethiopian commercial banks should invest in expand in new geographical area and also upscale their innovation leading to products attractive to consumers. Competition, which is the main industry specific factor affecting profitability, should be handled through well designed marketing strategy.